Lithium iron manganese phosphate positive electrode material and preparation method thereof, and electrochemical device

By blending the LMFP of small particles with LFP of large particles in lithium manganese iron phosphate positive electrode material, an efficient particle size grading is solved, and the compaction density and lithium ion diffusion rate of the material are improved, and the energy density and life of the battery are improved. abilities achieve comprehensive improvement of material performance.

CN118811790BActive Publication Date: 2024-12-31NANTONG RESHINE NEW MATERIAL TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411315332.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-31
Estimated Expiration
2044-09-20

AI Technical Summary

Technical Problem

Lithium manganese iron phosphate (LMFP) materials have problems with low compaction density and insufficient capacity in terms of performance, which limits the battery's energy density and endurance and hinders its large-scale commercial application.

Method used

By blending the LMFP of small particles with the LFP of large particles and controlling the particle size during the sintering process, the compaction density and lithium ion diffusion rate of the lithium iron manganese phosphate positive electrode material are improved, and efficient particle size grading is formed to ensure small Particles are filled in large particle gaps to improve the overall performance of the material.

Benefits of technology

The high compaction density and good electrochemical performance of lithium manganese iron phosphate cathode material are achieved, the energy density and charge and discharge efficiency are improved, and the problems of low compaction density and insufficient capacity are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118811790B_ABST
    Figure CN118811790B_ABST
Patent Text Reader

Abstract

A lithium iron manganese phosphate positive electrode material and a preparation method thereof, and an electrochemical device. The preparation method of the lithium iron manganese phosphate positive electrode material comprises mixing a lithium iron manganese phosphate material and a lithium iron phosphate material and sintering them to obtain the lithium iron manganese phosphate positive electrode material, wherein the median particle size D50 of the lithium iron manganese phosphate material is 0.15 μm to 0.35 μm, and the median particle size D50 of the lithium iron phosphate material is 0.8 μm to 1.2 μm. The preparation method fills small particles of lithium iron manganese phosphate into the gaps between large particles of lithium iron phosphate to form a lithium iron manganese phosphate positive electrode material with a large and small particle size distribution, so that the lithium iron manganese phosphate positive electrode material has both the stability of lithium iron phosphate and the high voltage performance of lithium iron manganese phosphate, and also has a high compaction density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of new energy, and specifically to a lithium iron manganese phosphate positive electrode material and a preparation method and an electrochemical device thereof. Background Art

[0002] As a lithium-ion cathode material, lithium manganese iron phosphate (LMFP) material combines the high voltage platform of manganese-based cathode materials and the high safety of iron-based cathode materials. Compared with lithium iron phosphate (LFP) materials, LMFP provides higher energy density; compared with nickel-cobalt-manganese ternary cathode materials, its watt-hour cost is lower and its safety is better, thus effectively solving some pain points of traditional cathode materials.

[0003] However, there are still some challenges in the performance of LMFP materials, such as low compaction density and insufficient capacity utilization. These problems limit the energy density of the battery, reduce the battery's energy output and endurance, and thus restrict the large-scale commercial application of LMFP materials. Summary of the invention

[0004] In view of this, in order to solve at least one of the above technical problems, an embodiment of the present application provides a method for preparing a lithium manganese iron phosphate positive electrode material.

[0005] In addition, the embodiments of the present application also provide a lithium iron manganese phosphate positive electrode material prepared by the aforementioned preparation method and an electrochemical device using the lithium iron manganese phosphate positive electrode material.

[0006] The present invention provides a method for preparing a lithium iron manganese phosphate positive electrode material, which comprises the following steps:

[0007] The lithium manganese iron phosphate (LMFP) material and the lithium iron phosphate (LFP) material are mixed and sintered to obtain the lithium manganese iron phosphate positive electrode material.

[0008] The median particle size D50 of the LMFP material is 0.15 μm to 0.35 μm, and the median particle size D50 of the LFP material is 0.8 μm to 1.2 μm.

[0009] In some possible embodiments, the method for preparing the LMFP material includes:

[0010] Mixing a manganese source, a first iron source, a first phosphorus source, a first lithium source and a first carbon source to obtain a first mixed material;

[0011] Grinding the first mixed material until the median particle size D50 of the particles is 0.15 μm to 0.45 μm to obtain a LMFP mixed material;

[0012] Sintering the LMFP mixed material to obtain a LMFP precursor; and

[0013] The LMFP precursor is ground until the median particle size D50 of the particles is 0.15 μm-0.35 μm to obtain the LMFP material, wherein the molar ratio of manganese element to iron element in the LMFP material is (1.5-4):1.

[0014] In some possible embodiments, the method for preparing the LFP material includes:

[0015] Mixing a second iron source, a second phosphorus source, a second lithium source and a second carbon source to obtain a second mixed material;

[0016] Grinding the second mixed material until the median particle size D50 of the particles is 0.8 μm to 1.2 μm to obtain an LFP mixed material;

[0017] Sintering the LFP mixture to obtain an LFP precursor; and

[0018] The LFP precursor is ground until the median particle size D50 of the particles is 0.8 μm to 1.2 μm to obtain the LFP material.

[0019] In some possible embodiments, the mass ratio of the LMFP material to the LFP material is (2.5-6):1; and / or

[0020] In the step of sintering the LMFP material and the LFP material, the sintering temperature is 500° C. to 850° C., the sintering time is 150 min to 500 min, and the heating rate is 1.5° C. / min to 5° C. / min.

[0021] In some possible embodiments, a first doping material is added to the first mixed material, and the doping element in the first doping material includes at least one of Mg, Ti, V, Nb, W, Mo, Er, Co, Ni and Al; and / or

[0022] In the step of grinding the first mixed material, grinding is performed in two steps. First, the first mixed material is ground until the median particle size D50 of the particles is 1.0 μm to 1.3 μm, and then ground until the median particle size D50 of the particles is 0.15 μm to 0.45 μm.

[0023] In some possible embodiments, a second doping material is added to the second mixed material, and the doping element in the second doping material includes at least one of Mg, Ti, V, Nb, W, Mo, Er, Co, Ni and Al; and / or

[0024] In the step of grinding the second mixed material, grinding is performed in two steps. First, the second mixed material is ground until the median particle size D50 of the particles is 1.3 μm to 1.5 μm, and then ground until the median particle size D50 of the particles is 0.8 μm to 1.2 μm.

[0025] In some possible embodiments, in the step of mixing the LMFP material and the LFP material, a third carbon source is further added, and the mass of the third carbon source is 3% to 10% of the total mass of the LMFP material and the LFP material.

[0026] An embodiment of the present application also provides a lithium iron manganese phosphate positive electrode material, which is prepared by the aforementioned method for preparing the lithium iron manganese phosphate positive electrode material. The lithium iron manganese phosphate positive electrode material includes LMFP particles and LFP particles, and the particle size of the LMFP particles is smaller than that of the LFP particles.

[0027] In some possible embodiments, the surface of the lithium manganese iron phosphate positive electrode material is further coated with a carbon coating layer.

[0028] An embodiment of the present application also provides an electrochemical device, which includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet includes the aforementioned lithium iron manganese phosphate positive electrode material.

[0029] Compared with the prior art, the preparation method of the lithium iron manganese phosphate positive electrode material provided in the embodiment of the present application is to mix large particles of LFP with small particles of LMFP, and the small particles of LMFP are filled in the gaps between the large particles of LFP, thereby improving the compaction density of the lithium iron manganese phosphate positive electrode material. In addition, because the selected graded large particles are LFP, the lithium ion diffusion rate in LFP is much higher than that of LMFP, which is beneficial to reduce the capacity loss caused by the larger particle size. Therefore, the lithium iron manganese phosphate positive electrode material obtained by grading large LFP particles and small LMFP particles has both the stability of LFP and the high lithium ion diffusion rate and the high voltage performance of LMFP, and also has a high compaction density and good electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 A process flow chart of the method for preparing the lithium iron manganese phosphate positive electrode material provided in an embodiment of the present application.

[0031] Figure 2 A schematic diagram of the structure of the electrochemical equipment of the lithium manganese iron phosphate positive electrode material provided in an embodiment of the present application.

[0032] Figure 3 This is a scanning electron microscope image of the lithium manganese iron phosphate positive electrode material provided in Example 1 and Comparative Example 1 of the present application. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments of the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.

[0034] The present invention provides a method for preparing a lithium iron manganese phosphate positive electrode material, which comprises the following steps:

[0035] The lithium manganese iron phosphate (LMFP) material and the lithium iron phosphate (LFP) material are mixed and sintered to obtain the lithium manganese iron phosphate positive electrode material, wherein the median particle size D50 of the LMFP material is 0.15μm~0.35μm, and the median particle size D50 of the LFP material is 0.8μm~1.2μm.

[0036] The preparation method of the embodiment of the present application is to mix the LMFP material with a smaller particle size (0.15μm~0.35μm) and the LFP material with a larger particle size (0.8μm~1.2μm) evenly, and then perform a sintering treatment to obtain a lithium iron manganese phosphate positive electrode material. Large particles of LFP and small particles of LMFP are graded (or mixed), and the small particles of LMFP can be evenly filled in the gaps between large particles of LFP, thereby improving the compaction density of the lithium iron manganese phosphate positive electrode material, thereby improving the energy density of the lithium iron manganese phosphate positive electrode material. At the same time, the large particle material selects LFP with a higher lithium ion diffusion rate, which can reduce the capacity loss of the lithium iron manganese phosphate positive electrode material and further improve the comprehensive performance of the lithium iron manganese phosphate positive electrode material.

[0037] Among them, the median particle size D50 of LMFP material is 0.15μm~0.35μm, and the median particle size of 0.15μm~0.35μm can shorten the lithium ion transmission distance and improve the charge and discharge capacity of LMFP material. When the median particle size D50 of LMFP material is too low (lower than 0.15μm), it will cause agglomeration of LMFP material, thereby affecting the consistency and stability of lithium manganese iron phosphate positive electrode material; when the median particle size D50 of LMFP material is too high (higher than 0.35μm), the lithium ion transmission distance in lithium manganese iron phosphate positive electrode material increases, the charge and discharge performance decreases, and the effect of particle size grading with LFP material is reduced. The median particle size D50 of the LMFP material may further be 0.2 μm to 0.3 μm, and may be 0.15 μm, 0.18 μm, 0.2 μm, 0.23 μm, 0.25 μm, 0.28 μm, 0.3 μm, 0.33 μm or 0.35 μm, etc. for example.

[0038] The median particle size D50 of LFP material is 0.8μm~1.2μm. The median particle size of 0.8μm~1.2μm helps to maintain good performance in lithium manganese iron phosphate positive electrode materials and form a particle size gradation with LMFP materials. When the median particle size D50 of LFP material is too low (lower than 0.8μm), the effect of particle size gradation with LFP material will be reduced; when the median particle size D50 of LFP material is too high (higher than 1.2μm), the lithium ion transmission distance in lithium manganese iron phosphate positive electrode materials will increase, the charge and discharge performance will decrease, and capacity loss will occur. The median particle size D50 of the LFP material can further be 0.9μm~1.1μm, and can be 0.8μm, 0.82μm, 0.85μm, 0.88μm, 0.9μm, 0.92μm, 0.95μm, 0.98μm, 1.0μm, 1.02μm, 1.05μm, 1.08μm, 1.1μm, 1.12μm, 1.15μm, 1.18 or 1.2μm, etc.

[0039] See also Figure 1 Specifically, the method for preparing the lithium manganese iron phosphate positive electrode material comprises the following steps:

[0040] Step S1: preparing the above LMFP material.

[0041] The preparation method of LMFP material may include the following steps:

[0042] Step S11, mixing a manganese source, a first iron source, a first phosphorus source, a first lithium source and a first carbon source to obtain a first mixed material.

[0043] In some embodiments, the molar ratio of manganese in the manganese source to iron in the first iron source can be (1.5-4):1, which is conducive to controlling the manganese-iron ratio in the final prepared lithium manganese iron phosphate positive electrode material within a reasonable range. The molar ratio of manganese in the manganese source to iron in the first iron source can further be (2-4):1, illustratively, it can be 1.5:1, 1.8:1, 2:1, 2.33:1, 2.5:1, 2.8:1, 3:1, 3.33:1, 3.5:1, 3.8:1 or 4:1, etc.

[0044] In some embodiments, the manganese source may include at least one of manganese oxide, manganese chloride, manganese sulfate, manganese carbonate, and manganese hydroxide, and the manganese oxide may include at least one of manganese dioxide and manganese tetraoxide.

[0045] In some embodiments, the first iron source may include at least one of iron oxide, iron hydroxide, iron phosphate, ferrous sulfate, and ferric chloride.

[0046] In some embodiments, the first phosphorus source may include at least one of iron phosphate, lithium dihydrogen phosphate, phosphoric acid, diammonium hydrogen phosphate, and ammonium dihydrogen phosphate.

[0047] In some embodiments, the first lithium source may include at least one of lithium carbonate, lithium oxalate, lithium hydroxide, and lithium acetate.

[0048] In some embodiments, the first carbon source may include at least one of starch, polyethylene glycol, salicylic acid, ethanol, methanol, citric acid, glucose, sucrose, and oxalic acid.

[0049] In some embodiments, in step S11, a first doping material may be added for mixing, and the doping element of the first doping material may include at least one of Mg, Ti, V, Nb, W, Mo, Er, Co, Ni and Al, etc. The introduction of the doping element can further improve the structural stability and ion diffusion rate of the lithium manganese iron phosphate positive electrode material.

[0050] Step S12, grinding the first mixed material until the median particle size D50 of the particles is 0.15 μm-0.45 μm, to obtain a LMFP mixed material.

[0051] In some embodiments, the grinding method in step S12 may include at least one of sand milling, high-energy ball milling, vibration milling, wall-breaking machine grinding, and soymilk machine grinding. It is understandable that grinding includes but is not limited to the above methods, and any method that can grind the first mixed material is acceptable.

[0052] In some embodiments, in step S12, grinding can be performed in two steps, first grinding until the median particle size D50 of the particles is 1.0 μm~1.3 μm, and then grinding until the median particle size D50 of the particles is 0.15 μm~0.45 μm.

[0053] For example, grinding can be a two-step grinding method using sand milling, specifically, the first mixed material is introduced into a sand mill for grinding, firstly coarse grinding (the diameter of the added zirconium beads is 0.6 mm) to 1.0 μm-1.3 μm, and then fine grinding (the diameter of the added zirconium beads is 0.3 mm) to 0.15 μm-0.45 μm. Sand milling can better control the particle size of the first mixed material.

[0054] In some embodiments, the first mixed material can be dissolved in the first solvent and mixed evenly before grinding, which can effectively improve the grinding effect. Furthermore, the first solvent can be water.

[0055] Step S13, sintering the LMFP mixed material to obtain a LMFP precursor.

[0056] In some embodiments, the LMFP mixed material can be spray dried before sintering, and spray drying is conducive to the volatilization of impurities and solvents. The spray drying inlet air temperature can be 200°C to 250°C, and the outlet air temperature can be 75°C to 120°C. Setting the range of the inlet air temperature and the outlet air temperature helps to control the volatilization rate and drying degree of the first solvent and impurities during the spray drying process. A higher inlet air temperature can further accelerate the volatilization of the first solvent, while a lower outlet air temperature helps to complete the drying with as little first solvent residue as possible.

[0057] In some embodiments, the sintering temperature in step S13 may be 500°C to 850°C, the sintering time may be 150min to 500min, and the sintering heating rate may be 1.5°C / min to 5°C / min. Under the above sintering conditions, a high-quality LMFP precursor with a stable crystal structure is formed.

[0058] Step S14, grinding the LMFP precursor until the median particle size D50 of the particles is 0.15 μm~0.35 μm, to obtain a LMFP material, wherein the molar ratio of manganese element to iron element in the LMFP material is (1.5~4):1.

[0059] The grinding method in this step may refer to the grinding method in the above step S112, and different particle sizes may be formed by adjusting the grinding parameters.

[0060] In some embodiments, in step S14, a first carbon source may be added to the LMFP precursor and then ground, which is beneficial to form a conductive network during the sintering process, thereby improving the conductivity of the final lithium manganese iron phosphate positive electrode material; in addition, the first carbon source can also form a carbon coating layer on the surface of the LMFP material, which helps to reduce the agglomeration of the LMFP material and ensure the fluidity of the LMFP material.

[0061] Step S2: preparing the above LFP material.

[0062] The preparation method of the LFP material may include the following steps:

[0063] Step S21, mixing a second iron source, a second phosphorus source, a second lithium source and a second carbon source to obtain a second mixed material.

[0064] In some embodiments, the second iron source may include at least one of iron oxide, iron hydroxide, iron phosphate, ferrous sulfate, and ferric chloride.

[0065] In some embodiments, the second phosphorus source may include at least one of iron phosphate, lithium dihydrogen phosphate, phosphoric acid, diammonium hydrogen phosphate, and ammonium dihydrogen phosphate.

[0066] In some embodiments, the second lithium source may include at least one of lithium carbonate, lithium oxalate, lithium hydroxide, and lithium acetate.

[0067] In some embodiments, the second carbon source may include at least one of starch, polyethylene glycol, salicylic acid, ethanol, methanol, citric acid, glucose, sucrose, and oxalic acid.

[0068] In some embodiments, in step S21, a second doping material may be added for mixing, and the doping element of the second doping material may include at least one of Mg, Ti, V, Nb, W, Mo, Er, Co, Ni, and Al. The introduction of doping elements can further improve the structural stability and ion diffusion rate of the lithium manganese iron phosphate positive electrode material.

[0069] Step S22, grinding the second mixed material to D50=0.8μm~1.2μm to obtain an LFP mixed material.

[0070] In some embodiments, the grinding method in step S22 may include at least one of sand milling, high-energy ball milling, vibration milling, wall-breaking machine grinding, and soymilk machine grinding. It is understood that grinding includes but is not limited to the above methods, and any method that can grind the second mixed material is acceptable.

[0071] In some embodiments, in step S22, the grinding may be a two-step grinding, first grinding until the median particle size D50 of the particles is 1.3 μm-1.5 μm, and then grinding until the median particle size D50 of the particles is 0.8 μm-1.2 μm.

[0072] For example, grinding can be a two-step grinding method using sand milling, specifically, the second mixed material is introduced into a sand mill for grinding, firstly coarse grinding (the diameter of the added zirconium beads is 0.6 mm) to 1.3 μm to 1.5 μm, and then fine grinding (the diameter of the added zirconium beads is 0.3 mm) to 0.8 μm to 1.2 μm. Sand milling can better control the particle size of the second mixed material.

[0073] In some embodiments, the second mixed material can be dissolved in the second solvent and mixed evenly before grinding, which can effectively improve the grinding effect. Furthermore, the second solvent can be water.

[0074] Step S23, sintering the LFP mixed material to obtain an LFP precursor, grinding the LFP precursor to D50 = 0.8 μm ~ 1.2 μm to obtain an LFP material.

[0075] In some embodiments, the LFP mixture can be spray dried before sintering, and spray drying is conducive to the volatilization of impurities and solvents. The spray drying inlet air temperature can be 200°C~250°C, and the outlet air temperature can be 75°C~120°C. Setting the range of the inlet air temperature and the outlet air temperature helps to control the volatilization rate and drying degree of the second solvent and impurities during the spray drying process. A higher inlet air temperature can accelerate the volatilization of the second solvent, while a lower outlet air temperature helps to complete the drying with as little second solvent residue as possible.

[0076] In some embodiments, the sintering temperature in step S23 may be 500° C. to 850° C., the sintering time may be 150 min to 500 min, and the sintering heating rate may be 1.5° C. / min to 5° C. / min. Under the above sintering conditions, a high-quality LFP precursor with a stable crystal structure is formed.

[0077] Step S24, grinding the LFP precursor until the median particle size D50 of the particles is 0.8 μm-1.2 μm, to obtain LFP material.

[0078] The grinding method in this step can refer to the grinding method in the above step S22.

[0079] In some embodiments, in step S24, a second carbon source may be added to the LFP precursor and then ground, which is beneficial to form a conductive network during the sintering process, thereby improving the conductivity of the final lithium iron manganese phosphate positive electrode material; in addition, the second carbon source can also form a carbon coating layer on the surface of the LFP material, which helps to reduce the agglomeration of the LFP material and ensure the fluidity of the LFP material.

[0080] The large-particle LFP material prepared in step S2 has a much higher lithium ion diffusion rate in LFP than in LMFP and lithium manganese phosphate (LMP). Therefore, even if the particle size of LFP is large, the capacity loss caused to LFP is small. In addition, the study found that even if LMFP with a lower manganese content is prepared into large particles and further graded with the above-mentioned small-particle LMFP, since LMFP is a solid solution of LFP and LMP, the lithium ion diffusion rate inside LMP in the large particles is extremely low, and some lithium ions cannot be transmitted to the particle surface over a long distance, resulting in a large capacity loss of the lithium iron manganese phosphate positive electrode material. Therefore, the present application mixes large particles of LFP with small particles of LMFP, which can effectively improve the compaction density and capacity of the lithium iron manganese phosphate positive electrode material.

[0081] Step S3, mixing the LMFP material and the LFP material and sintering them to obtain a lithium manganese iron phosphate positive electrode material.

[0082] Specifically, the LMFP material and the LFP material are mixed evenly and sintered under certain sintering conditions, followed by air flow pulverization and sieving to remove iron to obtain the lithium manganese iron phosphate positive electrode material.

[0083] Airflow milling can break the secondary balls formed after sintering, completely release the large particles of LFP material and the small particles of LMFP material, significantly improve the dispersion of the particles, and further make the large particles of LFP material and the small particles of LMFP material better mixed. In the subsequent compaction process of the lithium manganese iron phosphate cathode material, the refined and dispersed large particles of LFP material and small particles of LMFP material help to fill the space more evenly, thereby further improving the compaction density and overall performance of the lithium manganese iron phosphate cathode material.

[0084] In some embodiments, the mass ratio of LMFP material to LFP material can be (2.5-6):1, so as to adjust the composition of lithium manganese iron phosphate positive electrode material and achieve a balance between stability and high voltage performance of lithium manganese iron phosphate positive electrode material. The mass ratio of LMFP material to LFP material can further be (3-6):1, illustratively, it can be 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1 or 6:1, etc.

[0085] In some embodiments, when the LMFP material and the LFP material are mixed, a third carbon source may be added, which is not only beneficial for obtaining a uniform carbon coating layer, improving the structural stability of the lithium iron manganese phosphate positive electrode material, and controlling the particle size of the lithium iron manganese phosphate positive electrode material, but also beneficial for maintaining the particle size grading distribution between the LMFP material and the LFP material, thereby further improving the compaction density of the lithium iron manganese phosphate positive electrode material and reducing the resistivity of the lithium iron manganese phosphate positive electrode material.

[0086] In some embodiments, the mass of the third carbon source can be 3% to 10% of the total mass of the LMFP material and the LFP material, which is beneficial to further improve the compaction density, conductivity and structural stability of the lithium manganese iron phosphate positive electrode material. The mass of the third carbon source can further be 5% to 8% of the total mass of the LMFP material and the LFP material, and can be 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10% by way of example.

[0087] In some embodiments, the third carbon source may include at least one of starch, polyethylene glycol, salicylic acid, ethanol, methanol, citric acid, glucose, sucrose, and oxalic acid.

[0088] In some embodiments, the LMFP material and the LFP material can be spray dried after mixing, and spray drying is beneficial to the volatilization of impurities and solvents. The inlet air temperature of the spray drying can be 200°C to 250°C, and the outlet air temperature can be 75°C to 120°C. Setting the range of the inlet air temperature and the outlet air temperature helps to control the volatilization rate and drying degree of the solvent and impurities during the spray drying process. A higher inlet air temperature can accelerate the volatilization of the solvent, while a lower outlet air temperature helps to reduce the solvent residue.

[0089] In some embodiments, the sintering temperature in step S3 can be 500°C to 850°C. The sintering temperature will affect the particle size of the material, and the particle size directly affects the compaction density. Within the above temperature range, it is beneficial to control the growth of the particles. The sintering temperature can further be 650°C to 850°C, and can be 500°C, 550°C, 600°C, 650°C, 700°C, 750°C or 800°C, etc.

[0090] In some embodiments, the sintering time in step S3 may be 150 min to 500 min, which is conducive to the full sintering reaction. The sintering time may further be 300 min to 500 min, and may be 150 min, 180 min, 210 min, 240 min, 270 min, 300 min, 330 min, 360 min, 390 min, 420 min, 450 min, 480 min or 500 min, etc.

[0091] In some embodiments, the heating rate of sintering in step S3 may be 1.5°C / min to 5°C / min, which is conducive to uniform heating, avoiding excessive thermal stress, and preventing agglomeration caused by rapid heating. The heating rate of sintering may further be 1.5°C / min to 3.5°C / min, and may be 1.5°C / min, 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min, or 5°C / min, etc.

[0092] Compared with the prior art, the method for preparing the lithium manganese iron phosphate positive electrode material provided in the embodiment of the present application has the following beneficial effects:

[0093] 1. This application realizes the construction of different particle size distributions of lithium iron manganese phosphate positive electrode materials. The small particles of LMFP in the lithium iron manganese phosphate positive electrode materials are filled in the gaps between the large particles of LFP, so that the lithium iron manganese phosphate positive electrode materials have both the stability of LFP and the high voltage performance of LMFP, and also have a high compaction density. It creatively solves the pain point problems of low compaction density of lithium iron manganese phosphate positive electrode materials and significantly improves the energy density of lithium iron manganese phosphate positive electrode materials.

[0094] 2. In the process of preparing LFP and LMFP particles, a grinding process is used to control the particle size of the two particles. The mixture can be ground without destroying the performance of the material itself, and then further ground by a two-step method to more accurately control the particle size of the material.

[0095] 3. The addition of the first carbon source, the second carbon source and the third carbon source is not only conducive to obtaining a uniform carbon coating layer and improving the structural stability of the lithium iron manganese phosphate positive electrode material, but also can further control the particle size of the lithium iron manganese phosphate positive electrode material; in addition, the carbon source is also conducive to the mixed filling of large and small particles, thereby improving the compaction density of the lithium iron manganese phosphate positive electrode material.

[0096] An embodiment of the present application provides a lithium iron manganese phosphate positive electrode material, which is prepared by the aforementioned method for preparing the lithium iron manganese phosphate positive electrode material.

[0097] The positive electrode material includes LMFP particles and LFP particles, and the particle size of the LMFP particles is smaller than that of the LFP particles. The smaller particle size of the LMFP particles can improve the electrochemical activity of the lithium iron manganese phosphate positive electrode material, reduce the transmission distance of lithium ions in the lithium iron manganese phosphate positive electrode material, and thus improve the charging and discharging efficiency of the lithium iron manganese phosphate positive electrode material; the particle size of the LFP particles is larger than that of the LMFP particles, which helps to improve the overall conductivity and mechanical strength of the lithium iron manganese phosphate positive electrode material. Large particles of LFP are graded with small particles of LMFP, and small particles of LMFP are filled in the gaps between large particles of LFP, which improves the compaction density of the lithium iron manganese phosphate positive electrode material. At the same time, since the large particle material is LFP instead of LMFP, it is beneficial to reduce the capacity loss of the lithium iron manganese phosphate positive electrode material, and further improve the comprehensive performance of the lithium iron manganese phosphate positive electrode material.

[0098] In some embodiments, the surface of the lithium manganese iron phosphate positive electrode material may also be coated with a carbon coating layer, and the carbon coating layer is coated on the surface of the LMFP particles and the LFP particles. The carbon coating layer can form a conductive network to improve the properties of the lithium manganese iron phosphate positive electrode material, such as the conductivity and structural stability. When the carbon coating layer is located on the surface of the LMFP particles and the LFP particles, it can effectively prevent the particles from agglomerating, which is conducive to the LMFP particles filling the gaps between the LFP particles, thereby further improving the compaction density and volume specific capacity of the lithium manganese iron phosphate positive electrode material.

[0099] In some embodiments, the molar ratio of manganese to iron in the lithium iron manganese phosphate positive electrode material can be (0.25~2.18):1. The appropriate ratio of manganese to iron can optimize the capacity, rate performance and cycle life of the lithium iron manganese phosphate positive electrode material. Among them, the manganese element can improve the structural stability and conductivity of the lithium iron manganese phosphate positive electrode material, while the iron element helps to reduce production costs and improve the safety of the lithium iron manganese phosphate positive electrode material. The molar ratio of manganese element to iron element in the lithium manganese iron phosphate positive electrode material can further be (0.3~1.5):1, and can be 0.25:1, 0.3:1:, 0.33:1, 0.4:1, 0.45:1, 0.5:1, 0.55:1, 0.6:1, 0.65:1, 0.7:1, 0.75:1, 0.8:1, 0.85:1, 0.9:1, 0.95:1, 1:1, 1.3:1, 1.5:1, 1.55:1, 2:1 or 2.18:1, etc.

[0100] In some embodiments, the lithium iron manganese phosphate positive electrode material may contain doping elements, and the doping elements may be doped into the LMFP particles and / or the LFP particles. The doping elements may include at least one of Mg, Ti, V, Nb, W, Mo, Er, Co, Ni and Al, and may further be at least one of Mg and Ti. The doping elements may improve the structural stability of the lithium iron manganese phosphate positive electrode material, reduce the volume expansion and contraction of the lithium iron manganese phosphate positive electrode material during the charge and discharge cycle, and are also beneficial to the diffusion of ions in the lithium iron manganese phosphate positive electrode material and the improvement of conductivity.

[0101] Compared with the prior art, the lithium manganese iron phosphate positive electrode material provided in the embodiment of the present application has the following beneficial effects:

[0102] 1. In the lithium manganese iron phosphate positive electrode material, small particles of LMFP are filled in the gaps between large particles of LFP, so that the lithium manganese iron phosphate positive electrode material has both the stability of LFP and the high voltage performance of LMFP, as well as high compaction density and low capacity loss.

[0103] 2. The lithium manganese iron phosphate positive electrode material has a carbon coating layer, which is beneficial to improving the filling efficiency of LMFP particles and improving the conductivity and stability of the lithium manganese iron phosphate positive electrode material.

[0104] 3. The lithium iron manganese phosphate positive electrode material contains doping elements, which is beneficial to improving the structural stability and conductivity of the lithium iron manganese phosphate positive electrode material.

[0105] See also Figure 2As shown, an embodiment of the present application provides an electrochemical device (such as a battery), wherein the electrochemical device 100 includes a positive electrode sheet 10, a negative electrode sheet 20, a separator 30 and an electrolyte 40, wherein the separator 30 is arranged between the positive electrode sheet 10 and the negative electrode sheet 20, and the positive electrode sheet 10 includes the aforementioned lithium iron manganese phosphate positive electrode material.

[0106] Compared with the prior art, the electrochemical device 100 provided in the embodiment of the present application adopts the aforementioned lithium iron manganese phosphate positive electrode material, which effectively improves the energy density of the electrochemical device 100. Moreover, the aforementioned lithium iron manganese phosphate positive electrode material may contain doping elements and / or a carbon coating layer formed on the surface of the lithium iron manganese phosphate positive electrode material, which can effectively alleviate the structural damage of the positive electrode plate 10 caused by volume expansion during the charging and discharging process, maintain the integrity of the electrode structure, and avoid the rapid attenuation of the performance of the electrochemical device 100.

[0107] The above-mentioned lithium iron manganese phosphate positive electrode material and its preparation method are further described below through specific examples.

[0108] Example 1

[0109] Step 1, 11.35kg lithium carbonate, 42.8kg iron phosphate, 6kg glucose, 50kg manganese tetraoxide, 69.1kg lithium dihydrogen phosphate, 1.875kg magnesium carbonate, 0.150kg titanium dioxide, 0.516kg niobium pentoxide and 300kg water are mixed evenly to obtain a first mixed material (wherein the molar ratio of manganese to iron is 7:3); the first mixed material is introduced into a sand mill for coarse grinding (zirconium bead diameter 0.6mm), grinding particle size D50=1.3μm, and then introduced into a sand mill for fine grinding (zirconium bead diameter 0.3mm), grinding particle size D50=0.35μm, to obtain a LMFP mixed material; the LMFP mixed material is then spray dried, the spray drying inlet temperature is 220°C, the outlet temperature is 90°C, and then sintered under inert atmosphere protection conditions, the temperature is raised to 660°C at a rate of 2.5°C / min, and the temperature is kept for 7.5 hours, and finally cooled to obtain a LMFP precursor with a manganese to iron ratio of 7:3.

[0110] Step 2: 100 kg LMFP precursor, 3.5 kg glucose, 6.0 kg polyethylene glycol (molecular weight 6000) and 150 kg water were mixed and stirred evenly, and then introduced into a sand mill for coarse grinding (zirconium bead diameter 0.6 mm), and the coarse grinding was performed to a grinding particle size of D50 = 0.8 μm; and then introduced into a sand mill for fine grinding (zirconium bead diameter 0.3 mm), and the fine grinding was performed to a particle size of D50 = 0.28 μm to obtain LMFP material.

[0111] Step 3, 40.5kg lithium carbonate, 172kg iron phosphate, 14.6kg glucose, 1.5kg titanium dioxide and 300kg water are mixed evenly to obtain a second mixed material, the second mixed material is introduced into a sand mill for coarse grinding (zirconium bead diameter 0.6mm), grinding particle size D50=1.3μm, and then introduced into a sand mill for fine grinding (zirconium bead diameter 0.3mm), grinding particle size D50=0.9μm, to obtain an LFP mixed material; the LFP mixed material is then spray dried, the spray drying inlet air temperature is 220°C, the outlet air temperature is 90°C, and then sintered under inert atmosphere protection conditions, the temperature is raised to 660°C at a rate of 2.5°C / min, and the temperature is kept for 7.5 hours, and finally cooled to obtain an LFP precursor.

[0112] Step 4: 100 kg of LFP precursor, 3 kg of glucose, 6 kg of polyethylene glycol (molecular weight 6000) and 150 kg of water were mixed and stirred evenly, and then introduced into a sand mill for coarse grinding (zirconium bead diameter 0.6 mm) until the grinding particle size D50 = 0.9 μm to obtain LFP material.

[0113] Step 5, 50 kg of LMFP material and 20 kg of LFP material, that is, the mass ratio of LMFP material to LFP material is 5:2, and then spray drying is carried out after sufficient stirring for 1 hour. The spray drying inlet air temperature is 220°C and the outlet air temperature is 90°C. Then, sintering is carried out under inert atmosphere protection conditions, and the temperature is increased to 780°C at a rate of 2.5°C / min. The temperature is kept for 7.5 hours, and finally the temperature is cooled. Then, air flow crushing and iron removal are carried out at a grading wheel frequency of 120 Hz, and a manganese iron phosphate lithium positive electrode material with a manganese iron ratio of 5:5 is obtained.

[0114] Example 2

[0115] The specific process of the preparation process refers to Example 1, and the difference from Example 1 is that in step 5, the mass ratio of LMFP material to LFP material is 6:1, and a lithium iron manganese phosphate positive electrode material with a manganese-iron ratio of 6:4 is obtained. The preparation method of the remaining lithium iron manganese phosphate positive electrode material is basically the same as that in Example 1, and will not be described in detail here.

[0116] Comparative Example 1

[0117] Step 1: 12.85 kg lithium carbonate, 49.95 kg iron phosphate, 4.92 kg glucose, 25 kg manganese tetraoxide, 34.41 kg lithium dihydrogen phosphate, 1.14 kg magnesium carbonate, 0.0.091 kg titanium dioxide, 0.29 kg niobium pentoxide and 226 kg water are mixed uniformly to obtain a first mixed material (wherein the molar ratio of manganese to iron is 5:5); the first mixed material is introduced into a sand mill for coarse grinding (diameter of zirconium beads is 0.6 mm), and the grinding particle size D 50=1.1μm, and then introduced into a sand mill for fine grinding (zirconium bead diameter 0.3mm), grinding particle size D50=0.35μm, to obtain LMFP mixed material; then the LMFP mixed material was spray dried, the spray drying inlet air temperature was 220℃, the outlet air temperature was 90℃, and then sintered under inert atmosphere protection conditions, rising to 660℃ at a speed of 2.5℃ / min, keeping warm for 7.5 hours, and finally cooled to obtain a LMFP precursor with a manganese-iron ratio of 5:5.

[0118] Step 2: 100 kg LMFP precursor, 3.5 kg glucose, 6.0 kg polyethylene glycol (molecular weight 6000) and 150 kg water were mixed and stirred evenly, and then introduced into a sand mill for coarse grinding (zirconium bead diameter 0.6 mm), and the coarse grinding was performed to a grinding particle size of D50 = 0.9 μm; and then introduced into a sand mill for fine grinding (zirconium bead diameter 0.3 mm), and the fine grinding was performed to a particle size of D50 = 0.3 μm to obtain LMFP material.

[0119] Step 3: After the LMFP material is fully stirred for 1 hour, it is spray-dried. The spray drying inlet air temperature is 220°C and the outlet air temperature is 90°C. Then, it is sintered under inert atmosphere protection conditions, and the temperature is raised to 780°C at a rate of 2.5°C / min. It is kept warm for 7.5 hours, and finally cooled. Then, it is air-flow crushed and sieved to remove iron at a grading wheel frequency of 120Hz to obtain a lithium manganese iron phosphate positive electrode material with a manganese-iron ratio of 5:5.

[0120] Comparative Example 2

[0121] The specific process of the preparation process refers to Comparative Example 1. The difference from Comparative Example 1 is that the molar ratio of manganese to iron in the first mixed material in step 1 is 6:4, and the preparation method of the remaining lithium manganese iron phosphate positive electrode materials is basically the same as that in Comparative Example 1, which will not be described in detail here.

[0122] The following tests were performed on the lithium manganese iron phosphate positive electrode materials obtained in Example 1-2 and Comparative Example 1-2, and corresponding test results were obtained.

[0123] 1. The pH value, specific surface area, carbon content, powder compaction density, resistivity and electrical properties of the lithium manganese iron phosphate positive electrode materials obtained in Example 1-2 and Comparative Example 1-2 were tested. The results are shown in Table 1.

[0124] The specific test method is as follows:

[0125] (1) pH value: According to GB / T 24533-2019, the stable pH value of lithium manganese iron phosphate positive electrode material in water is tested.

[0126] (2) Specific surface area: Using the nitrogen adsorption-desorption method, at liquid nitrogen temperature, the equilibrium adsorption amount of nitrogen on the surface of an object is related to its specific surface area and other characteristics. Combined with the law of change of adsorption amount with relative pressure during the adsorption process, the specific surface area test can be carried out.

[0127] (3) Carbon content: The carbon content of lithium manganese iron phosphate positive electrode material is tested by infrared analysis. The sample is burned in a high-temperature, oxygen-rich state using a carbon-sulfur analyzer. The carbon element contained in it is oxidized into carbon dioxide and enters the infrared detector with the carrier gas. The carbon content is calculated by quantitatively analyzing the changes in the intensity of the infrared absorption wavelength of the carbon dioxide signal.

[0128] (4) Powder compaction density: Tested in accordance with the method specified in the standard drafted by the National Technical Committee for Standardization of Nonferrous Metals, "Determination of compaction density of lithium-ion battery positive electrode material powder".

[0129] (5) Powder resistivity test: The test is conducted in accordance with the method specified in the standard drafted by the National Technical Committee for Standardization of Nonferrous Metals, "Determination of Powder Resistivity of Positive Electrode Materials for Lithium-ion Batteries".

[0130] (6) Electrical performance test: The lithium iron manganese phosphate positive electrode materials in Example 1-2 and Comparative Example 1-2 were made into positive electrode sheets for button-type battery assembly. Metallic lithium was used as the negative electrode material. The assembled button-type battery was tested in the voltage range of 2.5~4.5V.

[0131] The test steps for the first charge and discharge efficiency include: at room temperature of 25°C, charge the lithium-ion battery at a constant current of 0.1C (C represents the current rate, 1C=2A) to 4.5V, then charge at a constant voltage until the current drops to 0.05C, stop charging, and record the first charge capacity; then discharge at 0.1C to a cut-off voltage of 2.5V, record the first discharge capacity, calculate the 0.1C specific capacity of the positive electrode material based on the first discharge capacity, and calculate the first charge and discharge efficiency of the battery, i.e., the first efficiency, according to the following formula: first charge and discharge efficiency = (first discharge capacity / first charge capacity)*100%.

[0132] Then, the above charging and discharging process was repeated once at a current of 1C, and the 2nd charging capacity and 2nd discharging capacity were recorded. The 1C specific capacity of the lithium manganese iron phosphate positive electrode material was calculated based on the 2nd discharge capacity.

[0133]

[0134] Example 1 and Comparative Example 1 are both lithium iron manganese phosphate positive electrode materials with a manganese-iron ratio of 5:5. By comparing the two, it can be seen that the lithium iron manganese phosphate positive electrode material in Comparative Example 1 has not formed a particle size gradation, and the compaction density is relatively low, only 2.37 g / cc, while the lithium iron manganese phosphate positive electrode material in Example 1 has a significantly improved compaction density due to the blending of large and small particles, specifically 2.51 g / cc; similarly, Example 2 and Comparative Example 2 are both lithium iron manganese phosphate positive electrode materials with a manganese-iron ratio of 6:4. The positive electrode material in Comparative Example 2 has not formed a particle size gradation, and the compaction density is relatively low, only 2.35 g / cc, while the positive electrode material in Example 2 has a significantly improved compaction density due to the blending of large and small particles, specifically 2.42 g / cc. This shows that since Examples 1-2 achieve efficient particle size grading, the filling effect makes the lithium manganese iron phosphate positive electrode material in Examples 1-2 more compact as a whole, and the compaction density is improved. At the same time, since the proportion of large particles in Example 1 is higher than that in Example 2, the compaction density of Example 1 is correspondingly higher.

[0135] The air flow crushing intensity and sintering temperature will affect the carbon content. High temperature sintering will reduce the carbon content of the lithium iron manganese phosphate positive electrode material. Too high air flow crushing intensity will also destroy the carbon coating layer on the surface of the lithium iron manganese phosphate positive electrode material. The carbon content of the lithium iron manganese phosphate positive electrode material in Examples 1-2 is within a suitable range, which is conducive to the uniform distribution of the carbon coating layer, thereby further reducing the powder resistivity of the lithium iron manganese phosphate positive electrode material.

[0136] The specific surface area of ​​the lithium iron manganese phosphate positive electrode material in Example 1-2 is significantly lower than that in Comparative Example 1-2. This is because more large particles are introduced in Example 1-2, and the number of small particles is reduced accordingly, and the specific surface area contributed by the small particles is correspondingly reduced. Therefore, the specific surface area of ​​the lithium iron manganese phosphate positive electrode material can be reduced, thereby improving the back-end processing performance of the lithium iron manganese phosphate positive electrode material.

[0137] In addition, when the graded large particles in the lithium manganese iron phosphate positive electrode material are LMFP, due to the large particle size, the lithium ion transmission distance increases, which will cause the electrochemical performance of the lithium manganese iron phosphate positive electrode material to deteriorate seriously. However, since the large particles introduced in the embodiment of the present application are LFP, the lithium ion diffusion rate in LFP is relatively high, which effectively alleviates this problem. It can be seen from the electrical performance data in Table 1 that the capacity and first effect of the positive electrode materials of Examples 1-2 are excellent. This shows that although the large particle structure of LFP will increase the lithium transmission path, these negative effects are reduced thanks to the large and small particle grading design of LFP and LMFP, so that the lithium manganese iron phosphate positive electrode material has excellent comprehensive performance.

[0138] 2. The lithium manganese iron phosphate positive electrode materials obtained in Example 1 and Comparative Example 1 were observed by scanning electron microscope. The results are as follows: Figure 3 shown.

[0139] By observation Figure 3 From the characterization of the morphology of the lithium iron manganese phosphate positive electrode material, it can be seen that the large particles in the lithium iron manganese phosphate positive electrode material in Example 1 are significantly increased, the large particles and small particles are mixed, and the small particles are evenly filled in the gaps between the large particles, thereby improving the compaction density of the lithium iron manganese phosphate positive electrode material.

[0140] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present invention, but the present invention is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be the present invention.

Claims

1. A method for preparing a lithium manganese iron phosphate positive electrode material, characterized in that: include: The lithium iron manganese phosphate material and the lithium iron phosphate material are mixed in a mass ratio of (2.5-6):1, and the temperature is raised to 500-850°C at a heating rate of 1.5°C / min-5°C / min for sintering for 150-500 minutes to obtain the lithium iron manganese phosphate positive electrode material. Wherein, the preparation method of the lithium iron manganese phosphate material comprises: Mixing a manganese source, a first iron source, a first phosphorus source, a first lithium source and a first carbon source to obtain a first mixed material; Grinding the first mixed material until the median particle size D50 of the particles is 0.15 μm to 0.45 μm to obtain a lithium manganese iron phosphate mixed material; Sintering the lithium iron manganese phosphate mixture to obtain a lithium iron manganese phosphate precursor; and Grinding the lithium iron manganese phosphate precursor until the median particle size D50 of the particles is 0.15 μm to 0.35 μm, to obtain the lithium iron manganese phosphate material, wherein the molar ratio of manganese element to iron element in the lithium iron manganese phosphate material is (1.5 to 4): 1; The preparation method of the lithium iron phosphate material comprises: Mixing a second iron source, a second phosphorus source, a second lithium source and a second carbon source to obtain a second mixed material; Grinding the second mixed material until the median particle size D50 of the particles is 0.8 μm to 1.2 μm to obtain a lithium iron phosphate mixed material; Sintering the lithium iron phosphate mixture to obtain a lithium iron phosphate precursor; and The lithium iron phosphate precursor is ground until the median particle size D50 of the particles is 0.8 μm to 1.2 μm to obtain the lithium iron phosphate material.

2. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: A first doping material is added to the first mixed material, wherein the doping element in the first doping material includes at least one of Mg, Ti, V, Nb, W, Mo, Er, Co, Ni and Al; and / or In the step of grinding the first mixed material, grinding is performed in two steps. First, the first mixed material is ground until the median particle size D50 of the particles is 1.0 μm to 1.3 μm, and then ground until the median particle size D50 of the particles is 0.15 μm to 0.45 μm.

3. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: A second doping material is added to the second mixed material, wherein the doping element in the second doping material includes at least one of Mg, Ti, V, Nb, W, Mo, Er, Co, Ni and Al; and / or In the step of grinding the second mixed material, grinding is performed in two steps. First, the second mixed material is ground until the median particle size D50 of the particles is 1.3 μm to 1.5 μm, and then ground until the median particle size D50 of the particles is 0.8 μm to 1.2 μm.

4. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: In the step of mixing the lithium iron manganese phosphate material and the lithium iron phosphate material, a third carbon source is further added, and the mass of the third carbon source is 3% to 10% of the total mass of the lithium iron manganese phosphate material and the lithium iron phosphate material.

5. A lithium manganese iron phosphate positive electrode material, characterized in that: The lithium iron manganese phosphate positive electrode material is prepared by the method for preparing the lithium iron manganese phosphate positive electrode material according to any one of claims 1 to 4.

6. The lithium iron manganese phosphate positive electrode material according to claim 5, characterized in that: The surface of the lithium manganese iron phosphate positive electrode material is also coated with a carbon coating layer.

7. An electrochemical device, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet comprises the lithium manganese iron phosphate positive electrode material as described in any one of claims 5 to 6.

Citation Information

Patent Citations

  • Preparation method of low-cost lithium iron phosphate and lithium manganese iron phosphate

    CN115196611A

  • Lithium manganese iron phosphate composite electrode plate as well as preparation method and application thereof

    CN116759540A

  • Lithium manganese iron phosphate composite positive electrode material as well as preparation method and application thereof

    CN117038971A

  • Composite lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof

    CN117542973A

  • Preparation method and application of lithium manganese iron phosphate material

    CN117658095A